THE IMPORTANCE OF THE DIAGNOSIS OF THE LACTIC DEHYDROGNEASE IN THE ASCIDE FLUID IN CIRRHOSIS AND GIS CARCINOMA - Naime CANORUÇ; Fikri CANORUÇ; Ramazan ÇİÇEK; Günel ULAK; Meltem ÖZDEN (Turkish Journal of Gastroenterology, 2020)
-